2014
DOI: 10.1167/iovs.14-14980
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Markers of Functional Phenotypic Corneal Endothelial Cells

Abstract: These markers will be useful for quality control to characterize the phenotype of cells destined for tissue engineering-based therapy. In addition, this selection protocol will provide a novel method for purification of functional cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 41 publications
2
67
0
2
Order By: Relevance
“…with that of Okumura et al 11 who found that CD166 was expressed in both normal cells and in fibroblastic cells. CD markers effective for distinguishing distinct SPs were selected by analyzing those on established cHCECs with a small cell area and a high cell density.…”
Section: Subpopulation Proven As Effector Cells In the Context Of CD supporting
confidence: 73%
See 4 more Smart Citations
“…with that of Okumura et al 11 who found that CD166 was expressed in both normal cells and in fibroblastic cells. CD markers effective for distinguishing distinct SPs were selected by analyzing those on established cHCECs with a small cell area and a high cell density.…”
Section: Subpopulation Proven As Effector Cells In the Context Of CD supporting
confidence: 73%
“…10 To date, no HCEC-specific cell surface markers have been elucidated, although two groups have reported the expression of CD markers. 11,12 The effector cell did not show any sign of surface CD200. Okumura et al 11 have reported that CD340, CD166, and CD98 are elevated in HCECs of nonfibroblastic phenotype, while CD9, CD49e, CD44, and CD73 are the indices of fibroblastic phenotypes.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations